Study on the effect of negative pressure occlusion drainage combined with silver ion dressing on inflammatory factors (IL-6, TNF-α) and healing effect of diabetic foot ulcer - Wang, Lu; Gao, Sheng-Feng; Jiang, Ya-Su; Chen, Peng; Gong, Zhen-Hua (Frontiers in Endocrinology, 2025)
BackgroundDiabetic foot ulcers impair quality of life and prognosis in diabetes. IL-6 and TNF-α regulate wound healing through inflammation. Although negative pressure wound therapy and silver dressings aid chronic wound repair, their combined efficacy in DFUs remains understudied.ObjectiveThis study aimed to assess how negative pressure occlusion drainage combined with silver ion dressing affects inflammatory cytokine levels (IL-6, TNF-α) and wound healing in patients with diabetic foot ulcer.MethodsThis study included 78 DFU patients treated with NPWT plus silver dressings (February 2023-April 2025). Serum IL-6 and TNF-α levels were measured at baseline, day 14, and day 30 post-treatment.ResultsThe findings indicated that IL-6 and TNF-α levels were significantly reduced at 14- and 30-days post-treatment compared to pre-treatment levels (P < 0.001), and the findings indicated a notable reduction in the wound area, with a healing duration of 19.49 ± 4.18 days and granulation tissue appearing in 6.83 ± 1.85 days. After 30 days of treatment, the healing rate reached 93.59%. The incidence of adverse reactions was low, 6.41%, and most of them were mild skin itching, nausea and vomiting, and a small amount of diarrhea.ConclusionNegative pressure occlusion drainage combined with silver ion dressing has potential advantages in reducing inflammatory response and promoting the healing of diabetic foot ulcers, which is worthy of clinical application. In the future, multicenter randomized controlled trials are needed to further verify its efficacy and safety.